2005
DOI: 10.1007/s00436-005-1314-x
|View full text |Cite
|
Sign up to set email alerts
|

IgG isotype to C-terminal 19�kDa of Plasmodium vivax merozoite surface protein 1 among subjects with different levels of exposure to malaria in Brazil

Abstract: Subclasses of antibodies to the C-terminal 19 kDa fragment of the Plasmodium vivax merozoite surface protein 1 (PvMSP-1(19)) were assessed among subjects with distinct degrees of malaria exposure in the Brazilian endemic area. The PvMSP-1(19) specific IgG1and IgG3 levels were low among subjects with long-term exposure (approximately 19 years) when compared to subjects less and sporadically exposed (<1 year). No statistically difference was observed in IgG subclass distribution of antibodies from symptomatic Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
28
2
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 28 publications
11
28
2
12
Order By: Relevance
“…2 and Table 3). This result is thus in agreement with the one reported previously for this portion of PvMSP1 (23). In contrast, immune sera from these same patients revealed a highly statistically significant association of antibodies against the N terminus of PvMSP1 with clinical protection and reduced risk of P. vivax infection over the 1-year follow-up period.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…2 and Table 3). This result is thus in agreement with the one reported previously for this portion of PvMSP1 (23). In contrast, immune sera from these same patients revealed a highly statistically significant association of antibodies against the N terminus of PvMSP1 with clinical protection and reduced risk of P. vivax infection over the 1-year follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…The criteria used to define asymptomatic individuals in these studies (Giemsa-positive or PCR-positive patients that did not develop symptoms after 72 h of this detection), however, is not stringent enough to discount the possibility that these could later turn into symptomatic patients. Regardless, the results suggested that there is an association of clinical protection with IgG1 subclass antibodies against the C terminus of P. falciparum (5), whereas no association with regard to antibodies or subclasses could be supported against the C terminus of P. vivax (23). In contrast to the above studies, we looked for associations of clinical protection and reduced risk of infection with serology against PvMSP1 in a human population in which symptomless P. vivax-infected individuals have been unarguably found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrasting with the extensive investigation of the role of Pf MSP-1 19 in naturally acquired immunity, little is known about the immune recognition of the ortholog protein of P. vivax (Pv). In Brazil, high proportions of subjects with detectable antibodies and T-cell responses to PvMSP-1 19 were found in areas of focal transmission (Soares et al 1997(Soares et al , 1999b and high proportions of seropositive subjects were uniformly observed in areas with more stable transmission (Morais et al 2005).…”
mentioning
confidence: 99%